STORAGE OF PIGLET KIDNEYS AT SUBNORMAL TEMPERATURES FOR PRIMARY TRYPSINIZED CELL MONOLAYER PREPARATION - B. L. Manin; N. V. Koropova; V. A. Starikov; I. V. Vologina (Ветеринария сегодня)
Optimization of the technology for preparation of the primary cells suitable for virological studies requires long-term storage of internal organs and tissues. Results of tests of organs stored at subnormal temperatures under laboratory conditions for the purpose of further preparation of complete monolayer of primary cells for their preservation are presented. Method for 6-day storage of kidneys aseptically taken from 3–5 month-old piglets was proposed. Serum-free medium 199 supplemented with 100 U/ml of penicillin, 100 µg/ml of streptomycin, 100 U/ml of gentamycin was used as a stabilizing substance. The organ was placed in a wide-neck vessel at medium/air phase ratio of 1:1 and the vessel was covered by a Petri dish to optimize medium chemical homeostasis and stored at temperature of –1 to +4 °C up to 6 days avoiding medium and organ crystallization. It was concluded that any freezing with crystallization and without cryoprotector (of –2 to –4 °С) had a negative eﬀect on cell and organ tissue survivability. Trypsinization and complete monolayer preparation were carried out upon the kidney storage period completion. All variants of prepared cell materials used for virological studies were suitable for testing semi-preparations for their avirulence as well as for virus neutralization tests and foot-and-mouth disease virus isolation. Proposed method for porcine kidney storage allows more eﬀective use of donor organs for primary culture preparation for virological studies. This method of organ storage could be recommended for preservation and transportation of organs derived from domestic and wild animals under feld conditions.